2011
DOI: 10.1155/2011/325789
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Alterations of Myelinated Fibers and Oligodendrocytes in the Prefrontal Cortex in Schizophrenia: A Postmortem Morphometric Study

Abstract: Schizophrenia is believed to result from altered neuronal connectivity and impaired myelination. However, there are few direct evidence for myelin abnormalities in schizophrenia. We performed electron microscopic study of myelinated fibers and oligodendrocytes and morphometric study of myelinated fibers in the prefrontal cortex in gray and white matters in schizophrenia and normal controls. Six types of abnormal fibers and ultrastructural alterations of oligodendrocytes were found in schizophrenia. No signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 65 publications
(63 reference statements)
6
106
0
9
Order By: Relevance
“…[42][43][44] First, postmortem studies have reported that significant reduction (14%-22%) in the density and the quantity of oligodendrocytes (cells producing myelin) [44][45][46][47][48][49][50][51][52][53][54][55][56] is seen alongside signs of apoptotic damage to myelin sheaths, 52,55,57 especially in the grey matter, and downregulation of myelin-related genes and proteins. [58][59][60][61][62][63][64] Arguably, of all the expressed brain proteins with recorded abnormalities, astrocytic and oligodendrocytic proteins appear to be the most consistently affected in patients with schizophrenia.…”
Section: The Role Of Myelin In Morphometrymentioning
confidence: 99%
“…[42][43][44] First, postmortem studies have reported that significant reduction (14%-22%) in the density and the quantity of oligodendrocytes (cells producing myelin) [44][45][46][47][48][49][50][51][52][53][54][55][56] is seen alongside signs of apoptotic damage to myelin sheaths, 52,55,57 especially in the grey matter, and downregulation of myelin-related genes and proteins. [58][59][60][61][62][63][64] Arguably, of all the expressed brain proteins with recorded abnormalities, astrocytic and oligodendrocytic proteins appear to be the most consistently affected in patients with schizophrenia.…”
Section: The Role Of Myelin In Morphometrymentioning
confidence: 99%
“…Reports of WM abnormalities in patients with schizophrenia are common and include reduced fractional anisotropy (FA) of water diffusion measured by diffusion tensor imaging (DTI) MRI (9-11) as well as reduced axonal myelin levels and glial cell density in postmortem brain studies (12)(13)(14). Identifying the key WM microstructural properties that explain the patient-control differences in processing speed may yield a specific quantitative target to evaluate treatments of cognitive and cerebral connectivity impairments in schizophrenia.…”
mentioning
confidence: 99%
“…Malfunction of oligodendrocyte development and demyelination have been considered as a pathological substrate for cognitive dysfunction inmultiple sclerosis (MS) and schizophrenia. 1,2 Therefore, identifying and manipulating the factors regulating oligodendrocyteprecursor cells (OPCs) proliferation and differentiation are crucial to the elucidation of pathological mechanisms of demyelination diseases.…”
Section: Introductionmentioning
confidence: 99%